The Relationship Between Academic Stress and Sleep Quality in Nursing Students at the Indonesian Muslim University - Jalil, Yeni Hasri Utami; Suhermi; Hidayat, Rahmat (Bantayang Omni Cendekia, 2025)
Background: Stress is a common part of student life due to various academic and personal demands. Academic stress, if not properly managed, can negatively impact sleep, a vital physiological process that supports physical, psychological, social, and cognitive functions. Objective: This study aimed to examine the relationship between academic stress and sleep quality among nursing students. Methods: An analytical descriptive study with a cross-sectional design was conducted among 51 nursing students from the class of 2024 at the Indonesian Muslim University. Academic stress and sleep quality were measured using validated questionnaires, and data were analyzed using the Chi-square test. Results: Among respondents, 33 students (64.7%) with mild academic stress reported poor sleep quality, while 10 students (19.6%) with mild stress had good sleep quality. Eight students (15.7%) with severe academic stress reported poor sleep quality, and no respondents with severe stress reported good sleep quality. Statistical analysis showed a significant association between academic stress and sleep quality (χ², p = 0.000 < 0.05). Conclusion: Academic stress is significantly associated with sleep quality among nursing students at the Indonesian Muslim University. It is recommended that students receive education on stress management strategies to reduce academic stress and its negative impact on sleep.